BUDAYA ADIL (JUST CULTURE) : UPAYA PENINGKATAN PELAPORAN INSIDEN KESELAMATAN PASIEN DI RUMAH SAKIT - Mustoha, Mustoha; Yuliaty, Farida; Paramarta, Vip; Kosasih, Kosasih (Jurnal Manajemen Kesehatan Indonesia, 2025)
Patient safety incidents are a critical issue in healthcare that can impact service quality and public trust in hospitals. Implementing a patient safety culture is one way to improve hospital services by raising awareness of error prevention and reporting. This study aims to improve reporting of patient safety incidents in the Central Surgical Installation of Mitra Plumbon Hospital, Cirebon, through the implementation of a culture of fairness. Using a quantitative, correlative descriptive method, this study involved 50 healthcare workers as respondents. The results showed a significant increase in reporting of patient safety incidents after the implementation of a culture of fairness, characterized by a shift from a moderate to a strong culture. A culture of fairness plays a crucial role in creating a safe work environment, where staff feel comfortable reporting incidents without fear of sanctions. This study is expected to contribute to efforts to improve patient safety in hospitals.